Ejercicios de la Universidad de Antioquia sobre números complejos, ecuaciones y propiedades de conjugados.

Question image

Understand the Problem

El problema presenta una serie de ejercicios de matemáticas que involucran números complejos, ecuaciones y propiedades de conjugados. Se pide realizar operaciones con números complejos, determinar la veracidad de igualdades, demostrar propiedades y resolver ecuaciones.

Answer

Solutions provided above.
Answer for screen readers

A.1.a) $\frac{9}{17} - \frac{15}{17}i$, product with conjugate: $\frac{18}{17}$ A.1.b) $\frac{11}{5} - \frac{2}{5}i$, product with conjugate: $5$ A.1.c) $\frac{-68}{15}-\frac{56}{15}i$, product with conjugate: $\frac{1552}{45}$ A.1.d) $1$, product with conjugate: $1$ A.1.e) $\frac{42}{7225} - \frac{13}{14450}i$, product with conjugate: $\frac{1}{28900}$ A.1.f) $-\frac{1}{50} - \frac{3}{200}i$, product with conjugate: $\frac{1}{1600}$ A.1.g) $1073741824$, product with conjugate: $1152921504606846976$

A.2.1) TRUE A.2.2) FALSE A.2.3) FALSE A.2.4) TRUE

A.3.a) Proof provided above A.3.b) Proof provided above

A.4.a) $x = 1$, $y = 2$ A.4.b) $x = -2$, $y = -1$

B.1.a) $x \neq \frac{1}{2}$ B.1.b) No solution B.1.c) $x = 0$ B.1.d) $t = 25$ B.1.e) $x = \frac{8}{27}$ and $x = -8$

Steps to Solve

  1. Solve A.1.a: $\frac{(5 + i) - (-1+7i)}{(2 - 3i) + (6 +5i)}$ Simplify the numerator and denominator separately $$ \frac{(5 + i) - (-1+7i)}{(2 - 3i) + (6 +5i)} = \frac{5 + i + 1 - 7i}{2 - 3i + 6 + 5i} = \frac{6 - 6i}{8 + 2i} $$ Multiply the numerator and denominator by the conjugate of the denominator: $$ \frac{6 - 6i}{8 + 2i} \cdot \frac{8 - 2i}{8 - 2i} = \frac{(6 - 6i)(8 - 2i)}{(8 + 2i)(8 - 2i)} = \frac{48 - 12i - 48i + 12i^2}{64 - 16i + 16i - 4i^2} $$ Since $i^2 = -1$: $$ \frac{48 - 60i - 12}{64 + 4} = \frac{36 - 60i}{68} = \frac{36}{68} - \frac{60}{68}i = \frac{9}{17} - \frac{15}{17}i $$ The complex number is $\frac{9}{17} - \frac{15}{17}i$ The conjugate of the complex number is $\frac{9}{17} + \frac{15}{17}i$ Calculate the product with its conjugate: $$ (\frac{9}{17} - \frac{15}{17}i)(\frac{9}{17} + \frac{15}{17}i) = (\frac{9}{17})^2 - (\frac{15}{17}i)^2 = \frac{81}{289} + \frac{225}{289} = \frac{306}{289} = \frac{18}{17} $$

  2. Solve A.1.b: $\frac{(1-2i)^{3}}{5i^{6}}$ Expand the numerator: $$ (1 - 2i)^3 = (1 - 2i)(1 - 2i)(1 - 2i) = (1 - 4i + 4i^2)(1 - 2i) = (1 - 4i - 4)(1 - 2i) = (-3 - 4i)(1 - 2i) = -3 + 6i - 4i + 8i^2 = -3 + 2i - 8 = -11 + 2i $$ Simplify the denominator: $$ 5i^6 = 5(i^2)^3 = 5(-1)^3 = -5 $$ Then divide: $$ \frac{-11 + 2i}{-5} = \frac{11}{5} - \frac{2}{5}i $$ The complex number is $\frac{11}{5} - \frac{2}{5}i$ The conjugate of the complex number is $\frac{11}{5} + \frac{2}{5}i$ Calculate the product with its conjugate: $$ (\frac{11}{5} - \frac{2}{5}i)(\frac{11}{5} + \frac{2}{5}i) = (\frac{11}{5})^2 - (\frac{2}{5}i)^2 = \frac{121}{25} + \frac{4}{25} = \frac{125}{25} = 5 $$

  3. Solve A.1.c: $[\frac{4+\sqrt{-81}}{5-\sqrt{-100}}]\cdot[\frac{\sqrt{-16}\sqrt{-25}}{\sqrt{-9}}]$ Simplify square roots: $$ \sqrt{-81}=9i, \sqrt{-100}=10i, \sqrt{-16}=4i, \sqrt{-25}=5i, \sqrt{-9}=3i $$ Substitute back into expression: $$ \frac{4+9i}{5-10i} \cdot \frac{(4i)(5i)}{3i} = \frac{4+9i}{5-10i} \cdot \frac{20i^2}{3i} = \frac{4+9i}{5-10i} \cdot \frac{-20}{3i} $$ Multiply by conjugate of $5-10i$: $$ \frac{4+9i}{5-10i} \cdot \frac{5+10i}{5+10i} = \frac{20 + 40i + 45i + 90i^2}{25 + 100} = \frac{20 + 85i - 90}{125} = \frac{-70 + 85i}{125} = \frac{-14+17i}{25} $$ Therefore, $$ \frac{-14+17i}{25} \cdot \frac{-20}{3i} = \frac{-14+17i}{25} \cdot \frac{-20}{3i} \cdot \frac{-i}{-i} = \frac{(-14+17i) \cdot 20i}{25 \cdot 3(-i^2)} = \frac{-280i + 340i^2}{75} = \frac{-340-280i}{75} = \frac{-68}{15}-\frac{56}{15}i $$ The complex number is $\frac{-68}{15}-\frac{56}{15}i$ The conjugate of the complex number is $\frac{-68}{15}+\frac{56}{15}i$ Calculate the product with its conjugate: $$ (\frac{-68}{15}-\frac{56}{15}i)(\frac{-68}{15}+\frac{56}{15}i) = (\frac{-68}{15})^2 - (\frac{56}{15}i)^2 = \frac{4624}{225} + \frac{3136}{225} = \frac{7760}{225} = \frac{1552}{45} $$

  4. Solve A.1.d: $(i^{3} +2i^{13})^{4}$ Simplify the expression inside the parenthesis. $i^3 = -i$ and $i^{13} = i^{12} \cdot i = (i^4)^3 \cdot i = 1^3 \cdot i = i$, so $$ (i^3 + 2i^{13})^4 = (-i + 2i)^4 = (i)^4 = 1 $$ The complex number is $1$ The conjugate of the complex number is $1$ Calculate the product with its conjugate: $$ 1\cdot 1 = 1 $$

  5. Solve A.1.e: $[(5i - 3)(2i+1)]^{-2}$ Simplify the expression inside the parenthesis. $$ (5i - 3)(2i + 1) = 10i^2 + 5i - 6i - 3 = -10 -i - 3 = -13 - i $$ Then we have $$ (-13 - i)^{-2} = \frac{1}{(-13 - i)^2} = \frac{1}{(-13 - i)(-13 - i)} = \frac{1}{169 + 13i + 13i + i^2} = \frac{1}{169 + 26i - 1} = \frac{1}{168 + 26i} $$ Multiply by the conjugate: $$ \frac{1}{168 + 26i} \cdot \frac{168 - 26i}{168 - 26i} = \frac{168 - 26i}{168^2 + 26^2} = \frac{168 - 26i}{28224 + 676} = \frac{168 - 26i}{28900} = \frac{168}{28900} - \frac{26}{28900}i = \frac{42}{7225} - \frac{13}{14450}i $$ The complex number is $\frac{42}{7225} - \frac{13}{14450}i$ The conjugate of the complex number is $\frac{42}{7225} + \frac{13}{14450}i$ Calculate the product with its conjugate: $$ (\frac{42}{7225} - \frac{13}{14450}i)(\frac{42}{7225} + \frac{13}{14450}i) = (\frac{42}{7225})^2 - (\frac{13}{14450}i)^2 = \frac{1764}{52200625} + \frac{169}{208802500} = \frac{67600+169}{208802500} = \frac{67769}{208802500} = \frac{1}{321} $$ Almost there, calculating it again $$ (\frac{42}{7225} - \frac{13}{14450}i)(\frac{42}{7225} + \frac{13}{14450}i) = (\frac{42}{7225})^2 + (\frac{13}{14450})^2 = \frac{1764}{52200625} + \frac{169}{208802500} = \frac{676 \cdot 4 + 169}{208802500} = \frac{2704+169}{208802500} = \frac{2873}{208802500} = \frac{1}{7267.3} $$ There must be some mistake here Let's go back $$ \frac{1}{168 + 26i} \cdot \frac{168 - 26i}{168 - 26i} = \frac{168 - 26i}{168^2 + 26^2} = \frac{168 - 26i}{28900} $$ The original number was $\frac{1}{(-13 - i)^2} = \frac{1}{(168 + 26i)} $ and conjugate is $\frac{1}{168 - 26i}$ Multiplying them gives: $$ \frac{1}{(168 + 26i)} \cdot \frac{1}{(168 - 26i)} = \frac{1}{168^2 + 26^2} = \frac{1}{28900} $$

  6. Solve A.1.f: $[(2+6i)^{2}]^{-1}$ $$ [(2+6i)^2]^{-1} = \frac{1}{(2+6i)^2} = \frac{1}{(2+6i)(2+6i)} = \frac{1}{4 + 12i + 12i + 36i^2} = \frac{1}{4 + 24i - 36} = \frac{1}{-32 + 24i} $$ Multiply by the conjugate: $$ \frac{1}{-32 + 24i} \cdot \frac{-32 - 24i}{-32 - 24i} = \frac{-32 - 24i}{(-32)^2 + (24)^2} = \frac{-32 - 24i}{1024 + 576} = \frac{-32 - 24i}{1600} = \frac{-32}{1600} - \frac{24}{1600}i = -\frac{1}{50} - \frac{3}{200}i $$ The complex number is $-\frac{1}{50} - \frac{3}{200}i$ The conjugate of the complex number is $-\frac{1}{50} + \frac{3}{200}i$ Calculate the product with its conjugate: $$ (-\frac{1}{50} - \frac{3}{200}i)(-\frac{1}{50} + \frac{3}{200}i) = (-\frac{1}{50})^2 - (\frac{3}{200}i)^2 = \frac{1}{2500} + \frac{9}{40000} = \frac{16 + 9}{40000} = \frac{25}{40000} = \frac{1}{1600} $$

  7. Solve A.1.g: $(-\frac{\sqrt{2}}{\frac{i}{2}})^{20}$ Simplify: $$ (-\frac{\sqrt{2}}{\frac{i}{2}})^{20} = (-\frac{2\sqrt{2}}{i})^{20} = (\frac{2\sqrt{2}}{-i})^{20} = (\frac{2\sqrt{2}}{-i} \cdot \frac{i}{i})^{20} = (\frac{2\sqrt{2}i}{-i^2})^{20} = (2\sqrt{2}i)^{20} = (2\sqrt{2})^{20} \cdot i^{20} $$ Note $i^{20} = (i^4)^5 = 1$, so we have: $$ (2\sqrt{2})^{20} = (2^{3/2})^{20} = 2^{30} = (2^{10})^3 = 1024^3 = 1073741824 $$ The complex number is 1073741824 The conjugate of the complex number is 1073741824 Calculate the product with its conjugate: $$ 1073741824 \cdot 1073741824 = 1152921504606846976 $$

  8. Determine if the equalities are true or false A.2.1: $|(6+3i) + (4+2i)| = |6 + 3i| + |4 + 2i|$ $$ LHS: |(6+3i) + (4+2i)| = |10 + 5i| = \sqrt{10^2 + 5^2} = \sqrt{100 + 25} = \sqrt{125} = 5\sqrt{5} $$ $$ RHS: |6 + 3i| + |4 + 2i| = \sqrt{6^2 + 3^2} + \sqrt{4^2 + 2^2} = \sqrt{36 + 9} + \sqrt{16 + 4} = \sqrt{45} + \sqrt{20} = 3\sqrt{5} + 2\sqrt{5} = 5\sqrt{5} $$ The equality is TRUE.

  9. Determine if the equalities are true or false A.2.2: $|3-2i| - |3+ 2i| = 4i$ $$ LHS: |3-2i| - |3+2i| = \sqrt{3^2 + (-2)^2} - \sqrt{3^2 + 2^2} = \sqrt{9 + 4} - \sqrt{9 + 4} = \sqrt{13} - \sqrt{13} = 0 $$ $$ RHS: 4i $$ Since $0 \neq 4i$, the equality is FALSE.

  10. Determine if the equalities are true or false A.2.3: $|3 - 2i| < |3+ 2i|$ $$ LHS: |3 - 2i| = \sqrt{3^2 + (-2)^2} = \sqrt{9 + 4} = \sqrt{13} $$ $$ RHS: |3 + 2i| = \sqrt{3^2 + 2^2} = \sqrt{9 + 4} = \sqrt{13} $$ Since $\sqrt{13} \nless \sqrt{13}$, the equality is FALSE.

  11. Determine if the equalities are true or false A.2.4: $|(3 – 2i) (3 + 2i)| = |3 - 2i||3 + 2i|$ $$ LHS: |(3 - 2i)(3 + 2i)| = |9 + 6i - 6i - 4i^2| = |9 + 4| = |13| = 13 $$ $$ RHS: |3 - 2i| |3 + 2i| = \sqrt{3^2 + (-2)^2} \sqrt{3^2 + 2^2} = \sqrt{13} \sqrt{13} = 13 $$ The equality is TRUE.

  12. Demonstrate the conjugate property A.3.a: $\overline{z \cdot w} = \overline{z} \cdot \overline{w}$ Let $z = a + bi$ and $w = c + di$, where $a,b,c,d \in R$. Then $\overline{z} = a - bi$ and $\overline{w} = c - di$. $$ z \cdot w = (a + bi)(c + di) = ac + adi + bci + bdi^2 = (ac - bd) + (ad + bc)i $$ $$ \overline{z \cdot w} = \overline{(ac - bd) + (ad + bc)i} = (ac - bd) - (ad + bc)i $$ On the other hand: $$ \overline{z} \cdot \overline{w} = (a - bi)(c - di) = ac - adi - bci + bdi^2 = (ac - bd) - (ad + bc)i $$ Since $\overline{z \cdot w} = (ac - bd) - (ad + bc)i$ and $\overline{z} \cdot \overline{w} = (ac - bd) - (ad + bc)i$, the equality $\overline{z \cdot w} = \overline{z} \cdot \overline{w}$ is TRUE.

  13. Demonstrate the conjugate property A.3.b: $\overline{z} = z$ if, and only if z is real. Let $z = a + bi$, where $a, b \in R$. The conjugate is $\overline{z} = a - bi$.

If $z$ is real, then $b = 0$, and $z = a$. Thus, $\overline{z} = a = z$. Conversely, if $\overline{z} = z$, then $a - bi = a + bi$, implies $-bi = bi$, and $2bi = 0$. Since $b$ is real, this implies $b = 0$. Thus $z = a$, which is real. Therefore, $\overline{z} = z$ if and only if $z$ is real.

  1. Determine the values of x and y in R that make the following expression true A.4.a: $(5-2i) - 7 = x - (3 + yi)$ $$ (5 - 2i) - 7 = x - (3 + yi) \implies -2 - 2i = x - 3 - yi $$ $$ -2 - 2i = (x - 3) - yi $$ Equating real and imaginary parts: $$ -2 = x - 3 \implies x = 1 $$ $$ -2 = -y \implies y = 2 $$ Thus, $x = 1$ and $y = 2$.

  2. Determine the values of x and y in R that make the following expression true A.4.b: $-6+ (3x + y)i = 3x + 7yi$ $$ -6+ (3x + y)i = 3x + 7yi $$ Equating real and imaginary parts: $$ -6 = 3x \implies x = -2 $$ $$ 3x + y = 7y \implies 3x = 6y \implies x = 2y $$ Since $x = -2$, $-2 = 2y \implies y = -1 $ Thus $x = -2$ and $y = -1$.

  3. Solve the equation B.1.a: $\frac{1}{2x-1} = \frac{4}{8x-4}$ $$ \frac{1}{2x-1} = \frac{4}{8x-4} = \frac{4}{4(2x-1)} = \frac{1}{2x-1} $$ The original equation is $\frac{1}{2x-1} = \frac{1}{2x-1}$. So, the equation is satisfied for any $x$ except for when if $2x-1=0$. $ 2x-1 \neq 0$ so $x \neq \frac{1}{2} $. Answer is all real numbers except $\frac{1}{2}$.

  4. Solve the equation B.1.b: $\sqrt{2x} - \frac{1}{\sqrt{2}} = \sqrt{8x}$ $$ \sqrt{2x} - \frac{1}{\sqrt{2}} = \sqrt{8x} = 2\sqrt{2x} \implies \sqrt{2x} - 2\sqrt{2x} = \frac{1}{\sqrt{2}} \implies -\sqrt{2x} = \frac{1}{\sqrt{2}} $$ $$ \sqrt{2x} = -\frac{1}{\sqrt{2}} $$ Since the square root cannot be negative, there is no solution.

  5. Solve the equation B.1.c: $\frac{3}{2x+3} + \frac{5}{2x-3} = \frac{4x +6}{4x^{2}-9}$ Note that $4x^2-9=(2x+3)(2x-3)$ Therefore $$ \frac{3}{2x+3} + \frac{5}{2x-3} = \frac{3(2x-3) + 5(2x+3)}{(2x+3)(2x-3)} = \frac{6x - 9 + 10x + 15}{4x^2 - 9} = \frac{16x + 6}{4x^2 - 9} $$ The equation becomes: $$ \frac{16x + 6}{4x^2 - 9} = \frac{4x +6}{4x^2 - 9} $$ Therefore, $$ 16x + 6 = 4x + 6 $$ $$ 12x = 0$$ $$ x = 0 $$ Also, $2x+3 \neq 0$ and $2x - 3 \neq 0$, thus $x \neq \pm\frac{3}{2}$. So since $x=0$ is not $\pm\frac{3}{2}$, the solution is $x = 0$.

  6. Solve the equation B.1.d: $\sqrt{10 + 3\sqrt{t}} = \sqrt{t}$ Square both sides $$ (\sqrt{10 + 3\sqrt{t}})^2 = (\sqrt{t})^2 $$ $$ 10 + 3\sqrt{t} = t$$ Let $u = \sqrt{t}$ then $u^2 = t$. The equation becomes: $$ 10 + 3u = u^2$$ $$ u^2 - 3u - 10 = 0$$ $$ (u-5)(u+2) = 0$$ So $u = 5$ or $u = -2$ Since $u = \sqrt{t}$, $u$ cannot be negative So $u=5$. So $5 = \sqrt{t}$, $t = 25$.

  7. Solve the equation B.1.e: $3x^{\frac{2}{3}} + 4x^{\frac{1}{3}} - 4=0$ Let $y=x^{\frac{1}{3}}$, then $y^2 = x^{\frac{2}{3}}$ Thus, $3y^2 + 4y - 4 = 0$. $$ (3y - 2)(y + 2) = 0$$ So $y = \frac{2}{3}$ or $y = -2$ If $y = \frac{2}{3}$, $x^{\frac{1}{3}} = \frac{2}{3} \implies x = (\frac{2}{3})^3 = \frac{8}{27} $ If $y = -2$, $x^{\frac{1}{3}} = -2 \implies x = (-2)^3 = -8 $ Thus $x = \frac{8}{27}$ and $x = -8$

A.1.a) $\frac{9}{17} - \frac{15}{17}i$, product with conjugate: $\frac{18}{17}$ A.1.b) $\frac{11}{5} - \frac{2}{5}i$, product with conjugate: $5$ A.1.c) $\frac{-68}{15}-\frac{56}{15}i$, product with conjugate: $\frac{1552}{45}$ A.1.d) $1$, product with conjugate: $1$ A.1.e) $\frac{42}{7225} - \frac{13}{14450}i$, product with conjugate: $\frac{1}{28900}$ A.1.f) $-\frac{1}{50} - \frac{3}{200}i$, product with conjugate: $\frac{1}{1600}$ A.1.g) $1073741824$, product with conjugate: $1152921504606846976$

A.2.1) TRUE A.2.2) FALSE A.2.3) FALSE A.2.4) TRUE

A.3.a) Proof provided above A.3.b) Proof provided above

A.4.a) $x = 1$, $y = 2$ A.4.b) $x = -2$, $y = -1$

B.1.a) $x \neq \frac{1}{2}$ B.1.b) No solution B.1.c) $x = 0$ B.1.d) $t = 25$ B.1.e) $x = \frac{8}{27}$ and $x = -8$

More Information

The solutions to the equations were found by using algebraic manipulations and properties of complex numbers and real numbers.

Tips

A common mistake when dealing with complex numbers is incorrectly applying the distributive property or not simplifying powers of $i$ correctly. For equations, a common mistake is not checking for extraneous solutions, especially when dealing with square roots. Another common mistake is sign errors when simplifying. Checking the work carefully helps to mitigate this.

AI-generated content may contain errors. Please verify critical information

Thank you for voting!
Use Quizgecko on...
Browser
Browser